Thermo-mechanical stability analysis of functionally graded shells. (1st January 2019) - Rezaiee-Pajand, M.; Pourhekmat, D.; Arabi, E.
Highlights: The thermo-elastic nonlinear analysis of various Functionally Graded shell is studied. The Voigt's model is adopted to define the Functionally Graded material properties. A six-noded isoparanetric triangular shell element is presented. The Euler-Rodrigues formulations and the first-order shear deformation theory are employed. Thermo-mechanical buckling of FG shell is predicted. Both the pre-buckling and post-buckling equilibrium paths are traced. Abstract: In this paper, the thermo-elastic nonlinear analysis of various Functionally Graded (FG) shells under different loading conditions is studied. A second-order isoparametric triangular shell element is presented for this purpose. The element is six-noded, and each node has all six independent degrees of freedom in space. It should be added, the first-order shear deformation theory is induced. Furthermore, Voigt's model is adopted to define the FG material properties, which are considered to change gradually from one surface to another. The critical temperature is predicted. Both the pre-buckling and post-buckling equilibrium paths are traced. Since the linear eigenvalue analysis leads to wrong responses in the problems with strong nonlinearity, the suggested procedure is performed based on the FEM and more exact estimations are achieved using equilibrium path.